Land inheritance and schooling in matrilineal societies: evidence from Sumatra - Quisumbing, Agnes R.; Otsuka, Keijiro (International Food Policy Research Institute, 2001)
This paper explores statistically the implications of the shift from communal to individualized tenure on the distribution of land and schooling between sons and daughters in matrilineal societies, based on a Sumatra case study. The inheritance system is evolving from a strictly matrilineal system to a more egalitarian system in which sons and daughters inherit the type of land that is more intensive in their own work effort. While gender bias is either non-existent or small in land inheritance, daughters tend to be disadvantaged with respect to schooling. The gender gap in schooling, however, appears to be closing for the generation of younger children.